The Effects of Low Concentrations of Nisin on Biofilm Formation by Staphylococcus aureus Isolated from Dairy Cattle - Edyta Kaczorek-Łukowska; Paweł Foksiński; Joanna Małaczewska; Roman Wójcik; Natalia Szyryńska (Pathogens)
Staphylococcus aureus is one of the aetiological agents of mastitis in dairy cattle. Their biofilms are relevant for human and veterinary medicine. It has been shown that some antibiotics at low concentrations can stimulate the production of biofilms, but there is little information on the effects of low concentrations of nisin, which is considered a therapeutic agent and has been added to food products for years as a biopreservative. In our study, we used Staphylococcus aureus strains (n = 28) isolated from dairy cattle. The MIC of nisin were determined using the broth microdilution method. Based on the minimum inhibitory concentration (MIC) results, the following concentrations were selected for further analyses: nisin at 39, 19, 9 IU/mL; nisin in combination with tetracycline at 39 IU/mL + 0.06 μg/mL, 18 IU/mL + 0.06 μg/mL, and 9 IU/mL + 0.06 μg/mL; and tetracycline alone at 0.06 μg/mL. The biofilm-forming capacity was determined via crystal violet staining in 96-well plates, icaD gene expression was determined using the 2−ΔΔCt method, and microscopic evaluation was carried out using scanning electron microscopy. Results: The MICs were 156 IU/mL (46%) and 312 IU/mL (43%) for most strains. Due to large statistical deviations, there were no statistically significant changes in the biofilm-forming capacity or icaD gene expression despite a visible increasing trend. Despite the absence of statistically significant differences, it was observed that for all concentrations analysed biofilm formation was noticeably greater for both nisin alone and for tetracycline and its mixtures than for untreated cells. Conclusions: In our opinion, the effects of nisin, especially at low concentrations, on biofilm structure show a certain worrying trend that may pose a future threat.